2021
DOI: 10.1093/jac/dkab324
|View full text |Cite
|
Sign up to set email alerts
|

Long-acting antiretrovirals: a new era for the management and prevention of HIV infection

Abstract: The long-acting antiretroviral cabotegravir and rilpivirine combination has just received FDA, EMA and Health Canada approval. This novel drug delivery approach is about to revolutionize the therapy of people living with HIV, decreasing the 365 daily pill burden to only six intramuscular injections per year. In addition, islatravir, a first-in-class nucleoside reverse transcriptase translocation inhibitor, is intended to be formulated as an implant with a dosing interval of 1 year or more. At present, long-act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 82 publications
0
58
0
1
Order By: Relevance
“…In this regard, therapeutic drug monitoring (TDM), which is current practice for some antibiotics, antiepileptics, immunosuppressants, antifungals, and anti-HIV drugs, may play a role for a particular subgroup of patients, such as people with BMI > 30 kg/m 2 , people with drug interaction problems, or elderly people with sarcopenia [28]. Indeed, if these patients show a substantially lower or higher minimum blood plasma concentration, in order to improve efficacy, a personalized dosing schedule could be designed,with a consequent decrease of the costs [29]. Cutrell et al demonstrated how virological failure in people treated with long-acting CAB/RPV had a multifactorial cause, but people with increased BMI, subtype A6/A1, and having at least two proviral RPV RAMs had an increased risk of failure [26].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, therapeutic drug monitoring (TDM), which is current practice for some antibiotics, antiepileptics, immunosuppressants, antifungals, and anti-HIV drugs, may play a role for a particular subgroup of patients, such as people with BMI > 30 kg/m 2 , people with drug interaction problems, or elderly people with sarcopenia [28]. Indeed, if these patients show a substantially lower or higher minimum blood plasma concentration, in order to improve efficacy, a personalized dosing schedule could be designed,with a consequent decrease of the costs [29]. Cutrell et al demonstrated how virological failure in people treated with long-acting CAB/RPV had a multifactorial cause, but people with increased BMI, subtype A6/A1, and having at least two proviral RPV RAMs had an increased risk of failure [26].…”
Section: Discussionmentioning
confidence: 99%
“…In their manuscript, Yu et al discussed assessing plasma concentrations (i.e., therapeutic drug monitoring) to guide patient management in the era of long-acting antiretrovirals, a sentiment that is echoed by others. 9 As the Food and Drug Administration approval for CAB-LA (and RPV-LA) currently stands, front-line clinicians are required to implement 1-size-fits-all dosing in patients who often do not conform to the controlled clinical trial settings in which the drugs were originally studied. The availability of drug concentrations for these clinicians would empower them to make informed decisions to manage these patients.…”
Section: In This Issue Of Thementioning
confidence: 99%
“…Secondary deposits are also formed within the lymphatic system, macrophages and T lymphocytes. As a result, the half-life of the nanocrystal preparations of CAB and RPV are 35-fold and 76-fold greater than their oral formulations respectively (Table 1)[6 ▪▪ ]. Novel prodrugs of CAB/RPV that could provide year-long exposure after a single injection are in the early stages of development.…”
Section: Long-acting Antiretroviral Therapy Regimens On the Horizonmentioning
confidence: 99%